2015
DOI: 10.3945/ajcn.114.106203
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of starch bioaccessibility in wheat endosperm to regulate starch digestion, postprandial glycemia, insulinemia, and gut hormone responses: a randomized controlled trial in healthy ileostomy participants

Abstract: Background: Cereal crops, particularly wheat, are a major dietary source of starch, and the bioaccessibility of starch has implications for postprandial glycemia. The structure and properties of plant foods have been identified as critical factors in influencing nutrient bioaccessibility; however, the physical and biochemical disassembly of cereal food during digestion has not been widely studied.Objectives: The aims of this study were to compare the effects of 2 porridge meals prepared from wheat endosperm wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 47 publications
6
125
0
1
Order By: Relevance
“…; Edwards et al . ). Enzymatic treatment and micro‐milling techniques designed to disrupt the aleurone cell walls enhance the release of iron from wheat flour during in vitro digestion and increase iron uptake by intestinal epithelial cells (Latunde‐Dada et al .…”
Section: Post‐harvest Improvements Of Iron and Zinc Bioavailabilitymentioning
confidence: 97%
“…; Edwards et al . ). Enzymatic treatment and micro‐milling techniques designed to disrupt the aleurone cell walls enhance the release of iron from wheat flour during in vitro digestion and increase iron uptake by intestinal epithelial cells (Latunde‐Dada et al .…”
Section: Post‐harvest Improvements Of Iron and Zinc Bioavailabilitymentioning
confidence: 97%
“…Barriers, including plant cell wall and protein matrices, prevent or slow down enzyme diffusion to substrate and thus alter the digestion rate. Previous studies have reported a reduction of glycemic responses (C. H. Edwards et al, 2015) and excretion of undigested macronutrients (Ellis et al, 2004;Noah et al, 1998;Tovar, Bjorck, & Asp, 1992) on consumption of whole grains or cooked legumes in humans and rats. The in vitro digestion rate of starch and lipids was reduced due to the intact cell walls (Dhital, Bhattarai, Gorham, & Gidley, 2016;C.…”
Section: Access To Starch Substratementioning
confidence: 97%
“…; Edwards et al . ). Thus, a combination of physical inaccessibility of minerals encapsulated by plant cell walls, the removal of aleurone during milling, poor bioavailability of currently used fortificants and high levels of inhibitory phytates and phenolic compounds (Hallberg et al .…”
Section: Current Fortification Strategiesmentioning
confidence: 97%